Activity-dependent endocytic sorting of kainate receptors to recycling or degradation pathways - Martin, Stéphane (Nature Publishing Group, 2004)
Kainate receptors (KARs) play important roles in the modulation of neurotransmission and plasticity, but the mechanisms that regulate their surface expression and endocytic sorting remain largely unknown. Here, we show that in cultured hippocampal neurons the surface expression of GluR6-containing KARs is dynamically regulated. Furthermore, internalized KARs are sorted into recycling or degradative pathways depending on the endocytotic stimulus. Kainate activation causes a Ca(2+)- and PKA-independent but PKC-dependent internalization of KARs that are targeted to lysosomes for degradation. In contrast, NMDAR activation evokes a Ca(2+)-, PKA- and PKC-dependent endocytosis of KARs to early endosomes with subsequent reinsertion back into the plasma membrane. These results demonstrate that GluR6-containing KARs are subject to activity-dependent endocytic sorting, a process that provides a mechanism for both rapid and chronic changes in the number of functional receptors.